Sosialisasi Sadar Lingkungan Dan Pengadaan Tong Sampah Di RT.10 Rw.02 Kelurahan Betungan - Romanza, Nano; Pratama, Rendi; Putri, Shintia; Ramadani, Cindy; Saputra, Deni; Herlyaminda, Evi; Fitriano, Yun; Susanti, Neri (Jurnal Dehasen Untuk Negeri, 2025)
Environmental problems due to household waste are one of the important issues in residential areas. This Community Service (KKN) activity aims to increase public awareness of the importance of maintaining environmental cleanliness through environmental awareness socialization and provision of trash cans. The target of the activity is residents of RT 10 RW 02, Betungan Village, Bengkulu City. The implementation method is in the form of counseling, group discussions, and direct provision of facilities in the form of separate trash cans (organic and inorganic). The results of the activity showed the enthusiasm of residents in participating in the socialization and the beginning of the habit of disposing of trash according to its type. This program is expected to be the first step in realizing a clean and healthy environment in a sustainable manner.